Experience of unilateral and bilateral transpedicular fixation in degenerative diseases of the lumbar spine - V. A. Sorokovikov; V. E. Potapov; A. P. Zhivotenko; A. V. Gorbunov; O. V. Sklyarenko; S. N. Larionov (Acta Biomedica Scientifica, 2023)
The aim. To study the effectiveness of using monosegmental fixation systems in surgeries involving resection of part of the facet joint in patients with posterolateral and foraminal hernias in the lumbar spine.Materials and methods. The study included 40  patients with degenerative diseases of the lumbar spine who underwent medial facet resection and the removal of posterolateral or foraminal disc hernia. Among them, 10  patients underwent unilateral single-level transpedicular fixation with interbody fusion using titanium cage (UTPF cage group), and the other 10 patients underwent unilateral monosegmental transpedicular fixation (UTPF group). The remaining 20 patients underwent bilateral transpedicular fixation (BTPF group). The amount of intraoperative blood loss, duration of surgery and length of hospital stay, as well as the frequency of perioperative complications in the groups were assessed. Visual analogue scale (VAS) pain score, Oswestry index and McNab score were assessed before and 6 and 12 months after surgery.Results. Intraoperative blood loss in the UTPF  cage and UTPF groups was less than in the BTPF group, as was the duration of surgery; the differences were statistically significant (p < 0.05). Indicators of VAS score and Oswestry Quality of Life Index in the studied groups indicated the effectiveness of the technology.Discussion. Unilateral decompressive and stabilizing surgeries in patients with posterolateral and foraminal hernias of the lumbar spine can reduce the duration of the surgery, the volume of blood loss and the severity of pain in the postoperative period due to adequate decompression of the neurovascular formations of the spinal canal and stabilization of the spinal motion segment, which prevents the relapse of the disease and provides early rehabilitation of patients.Conclusion. Unilateral transpedicular fixation is acceptable and safe for lumbar degenerative diseases and improves the quality of life of the patients.